GTH 2025 ARTE: The Art in Science – Curiosity and Creativity - Albisetti, Manuela; Alberio, Lorenzo (Hämostaseologie, 2025)
The 2025 Annual Congress of the Society of Thrombosis and Haemostasis Research (GTH) takes its inspiration from ARTE—Advances, Research, Technology, and Education in the field of thrombosis and hemostasis. The numerous scientific contributions of the congress highlight the most recent progresses in this field, and reveal the profound connection between the rigor of science and the beauty of human creativity. ARTE, the Italian word for “art,” refers to the deep synergy existing between analytical precision and imaginative expression, which is vividly reflected in this year's contributions to our themed congress issue.